Construction planning, equipment, and methods - Peurifoy, Robert L.; Peurifoy, Robert L.; Schexnayder, Clifford J.; Schmitt, Robert L.; Shapira, Aviad (McGraw-Hill, 2018)
Follows in the footsteps of previous editions by laying out the fundamentals of machine utilization and production estimating in a logical, simple, and concise format. The book discusses the latest technologies and capabilities and offers real-world applications. Examples and illustrations showcase the latest equipment models and end-of-chapter summaries and homework problems reinforce salient points. You will explore construction economics, earthwork, and soil and rock properties. Safety procedures and financial considerations are thoroughly explained in this comprehensive guide.